What Factors Are Associated with Good Performance in Children with Cochlear Implants? From the Outcome of Various Language Development Tests, Research on Sensory and Communicative Disorders Project in Japan: Nagasaki Experience - Yukihiko Kanda; Hidetaka Kumagami; Minoru Hara; Yuzuru Sainoo; Chisei Sato; Tomomi Yamamoto-Fukuda; Haruo Yoshida; Akiko Ito; Chiharu Tanaka; Kyoko Baba; Ayaka Nakata; Hideo Tanaka; et al. (Clinical and Experimental Otorhinolaryngology, 2012)
ObjectivesWe conducted multi-directional language development tests as a part of the Research on Sensory and Communicative Disorders (RSVD) in Japan. This report discusses findings as well as factors that led to better results in children with severe-profound hearing loss.MethodsWe evaluated multiple language development tests in 33 Japanese children with cochlear implants (32 patients) and hearing aid (1 patient), including 1) Test for question and answer interaction development, 2) Word fluency test, 3) Japanese version of the Peabody picture vocabulary test-revised, 4) The standardized comprehension test of abstract words, 5) The screening test of reading and writing for Japanese primary school children, 6) The syntactic processing test of aphasia, 7) Criterion-referenced testing (CRT) for Japanese language and mathematics, 8) Pervasive development disorders ASJ rating scales, and 9) Raven's colored progressive matrices. Furthermore, we investigated the factors believed to account for the better performances in these tests. The first group, group A, consisted of 14 children with higher scores in all tests than the national average for children with hearing difficulty. The second group, group B, included 19 children that scored below the national average in any of the tests.ResultsOverall, the results show that 76.2% of the scores obtained by the children in these tests exceeded the national average scores of children with hearing difficulty. The children who finished above average on all tests had undergone a longer period of regular habilitation in our rehabilitation center, had their implants earlier in life, were exposed to more auditory verbal/oral communication in their education at affiliated institutions, and were more likely to have been integrated in a regular kindergarten before moving on to elementary school.ConclusionIn this study, we suggest that taking the above four factors into consideration will have an affect on the language development of children with severe-profound hearing loss.